Antidiabetic, anti-inflammatory and antioxidant activity of Artemisia Roxburghiana along with its qualitative and quantitative phytochemical Screening - Bibi, Sadia; Ahmed, Zahoor; Dilawar, Shahnaz; Iqbal, Muhammad; Sheikh, Shahzad H; Khalid, Sumbal; Ahmad, Muhammad Tayyab (ADVANCES IN BASIC MEDICAL SCIENCES, 2021)
Objective The objective of study was to conduct different assays for exploring pharmacological properties of medicinal plant Artemisia roxburghiana along with its phytochemical screening. Methodology Qualitative and quantitative tests phytochemical were carried out using different methods for total phenolic and flavonoid contents. Antioxidants capacity, total reducing power assay (TRP) and total antioxidant capacity (TAC) were determined. Formalin induced right hand paw edema method was used for investigation of anti-inflammatory activity. The anti-diabetic study was done by both in-vitro (Î± amylase inhibition assay) and in-vivo (Alloxan induced anti-diabetic study). Results The plant revealed the presence of active primary and secondary phytochemicals and exhibits significant anti-oxidant, anti-diabetic and anti-inflammatory activities. Radial scavenging activity (2, 2’-Diphenyl Picrylhydrazyl radical scavenging activity), total antioxidant capacity (TAC), and total reducing power (TRP) of Artemisia roxburghiana extracts at final concentration of 400 Î¼g/mL is considerably significant. The presence of alkaloids, phenolic, flavonoids, terpenoids, reducing sugars, glycosides, steroids, carbohydrates and steroids was seen in all the extracts as well as effects of amylase etc. Conclusion This plant is a source of valuable natural products for pharmaceutical industries and can be used for identification and isolation of novel compounds which leads toward drug discovery for treatment of more serious and complicated diseases. Keywords Artemisia, Antidiabetic, DPPH, Antiinflammatory, TAC, Alloxan, Formalin